A sodium dichloroisocyanurate-based conditioning process for the improvement of sludge dewaterability and mechanism studies. (15th April 2021) - Dong, Yanting; Shen, Yanwen; Ge, Dongdong; Bian, Chang; Yuan, Haiping; Zhu, Nanwen
Abstract: Sludge dewatering is necessary to reduce the volume of sludge for cost-effective transport and ultimate disposal. In this study, a novel combined chemical conditioning process was proposed to improve sludge dewatering performance in which sludge flocs were destructed by sodium dichloroisocyanurate (DCCNa) and re-flocculated by Al2 (SO4 )3 and the mechanism was elucidated. The results showed that sludge capillary suction time (CST) dropped to 15.4 s and moisture content of dewatered sludge cake (Mc) deceased to 71.01% respectively, after the application of combined conditioning with the optimal dosage of 200 mg DCCNa/g dry solids (DS) and 80 mg Al2 (SO4 )3 /g DS. With chemical conditioning, sludge physicochemical properties were greatly changed. With the DCCNa application, the percentage of low-molecular-weight substances in soluble extracellular polymeric substances (S-EPS) increased. Also, the sludge zeta potential dropped from −16.85 mV to −25.45 mV and the median particle size (D50) decreased from 54.1 μm to 51.6 μm. However, the subsequent conditioning by Al2 (SO4 )3 dosing not only led to an increment of 18% in the portion of macromolecules in S-EPS, but also increased the zeta potential and D50 to −10.74 mV and 53.2 μm, respectively. The bound water content in sludge declined from 2.92 g/g DS to 1.98 g/g DS after combined conditioning. We concluded that DCCNa disintegrated the sludge flocs and microbial cells leading to the release of bound water, fine particles and organic substances with negative charge, and the fine colloidal particles can be flocculated into large dense aggregations with the dosing of Al2 (SO4 )3 . In summary, the proposed combined conditioning provided a highly effective and environmental friendly approach to improve the sludge dewatering performance. Graphical abstract: Image 1 Highlights: DCCNa and Al2 (SO4 )3 were applied to promote sludge dewatering. Bound water was largely released via porous structure of conditioned sludge. Flocs destruction and re-floccucation were responsible for excellent dewaterability.